How do our eyes see? - Ballard, Carol (Austin, Tex. : Raintree Steck-Vaughn, 1998)
A basic introduction to how our bodies see, exploring such topics as light and dark, color, and glasses.
Includes bibliographical references (p. 31) and index.
Keywords: Vision -- Juvenile literature; Vision; Eye; Senses and sensation